Chemotherapeutic Effectiveness of Combining Cetuximab for Metastatic Colorectal Cancer Treatment: A System Review and Meta-Analysis - Rong Li; Minqing Liang; Xiao Liang; Lu Yang; Min Su; Keng Po Lai; Keng Po Lai (Frontiers in Oncology, 2020)
This meta-analysis used the database including PubMed, Medline, Cochrane Library, CNKI, Chinese-Cqvip, and Wanfang for randomized controlled trials (RCTs) to investigate the clinical effectiveness for combining cetuximab treatment with chemotherapy for treating metastatic colorectal cancer (mCRC). A total of 12 RCTs involved 7,108 patients with mCRC were included. The patients received chemotherapy with (3,521 cases) or without cetuximab (3,587 cases). Outcomes were overall survival (OS), progression-free survival (PFS), disease control rate (DCR), overall response rate (ORR), odd ratio (OR), and risk ratio (HR). Our results showed that the chemotherapy alone group has shorter OS, PFS, and ORR than the chemotherapy plus cetuximab group, with significant differences (PFS:HR = 0.77, 95% CI = 0.72–0.82, P < 0.00001; OS:HR = 0.88, 95% CI = 0.79–0.99, P = 0.03; ORR:OR = 1.79, 95% CI = 1.30–2.47; P = 0.0003). Results of subgroup analysis showed that cetuximab treatment prolonged PFS and OS in KRAS wild-type patients, with statistically significant differences (PFS:HR = 0.79, 95% CI = 0.65–0.95, P = 0.01; OS:HR = 0.85, 95% CI = 0.74–0.98, P = 0.02). Combining cetuximab with chemotherapy, the PFS and OS of wild-type KRAS patients and the ORR of all patients were significantly improved.